La masificación del baloncesto en las niñas de 10 a 14 años de edad, de la parroquia Quilanga, cantón Quilanga de la provincia de Loja, en el año 2019-2020 - Condolo Castillo, Jorge Luis (2021)
The present investigation titled: The Massification of Basketball in Girls 10 to 14 Years Old, From Quilanga Parish, Quilanga Canton of the Loja Province, In the Year 2019-2020, whose problem was raised: How the lack of Motivation and sports organization causes the ignorance of the massification of basketball in girls aged 10 to 14 as a means of sports integration ?, the general objective that has been proposed is to promote the development of strategies for the massification of Basketball in girls from From 10 to 14 years, from this, the teaching-learning of the technical foundations of basketball was proposed, in the categories of basketball and mini-basketball through workshops. During the process, the methods were applied; scientific, descriptive, inductive, statistical observation, techniques such as observation, survey and interview, instruments such as the observation sheet to know the mastery of the technical fundamentals of basketball at the beginning and at the end. It was concluded that lack of motivation and sports disorganization together with the scarce support of parents, as well as the excessive use of cell phones do not allow girls to practice basketball in their free time, in addition to basketball training being insufficient and discontinuous due to the scarce economic resources of the sports entity in charge, in addition the initial diagnosis in the execution of the technical foundations of basketball presents a deficiency in the application, while the final diagnosis in the execution presents an excellent knowledge and execution of the themselves, for which it was identified that basketball workshops promote the practice of basketball in girls between 10 and 14 years old, motivated to learn the basic technical foundations for its execution in competitions.